Enteroaggregative E. coli O104 from an outbreak of HUS in Germany 2011, could it happen again? - Marie Anne Chattaway; Tim Dallman; Iruka N Okeke; John Wain (Journal of Infection in Developing Countries)
Enterohaemorrhagic E. coli (EHEC) particularly O157:H7 (Sequence type 11 complex), is the best documented and most well-known of E. coli that cause diarrhoea. The importance of EHEC lies in the severity of disease. Outbreaks can infect thousands of people causing bloody diarrhoea and haemolytic uremic syndrome (HUS) that in turn can result in protracted illness or even death. The ability of EHEC to colonise the human gut is normally associated with the presence of genes from another group of diarrhoeagenic E. coli, the enteropathogenic E. coli (EPEC), via the locus of enterocyte effacement. However, the massive outbreak in Germany was caused by an EHEC which had acquired virulence genes from yet another group of diarrhoeagenic E. coli, the enteroaggregative E. coli (EAEC). In reality EAEC is probably the most common bacterial cause of diarrhoea but is not identified in most diagnostic laboratories. This outbreak emphasises the importance of being able to detect all diarrhoeagenic E. coli and not to focus on E. coli O157:H7 alone. Routine surveillance systems for EAEC, a once ignored global pathogen, would go a long way to reaching this goal. This review describes methods for identifying non-O157 EHEC and describes the key genetic features of EHEC and EAEC. Our aim is to provide information for laboratories and policy makers which enables them to make informed decisions about the best methods available for detecting newly emergent strains of diarrhoeagenic E. coli.